Keywords; : For Further Consideration and Particularly Relevant to Academic Life, &c. (Book collections on Project MUSE., 2017)
An irreverent critical lexicon of academic life and cultureThe university: The very name evokes knowledge, culture, and the magnificently universal ambition at the heart of this essential institution. Bastions of free inquiry and a free society, engines of social transformation and economic progress, enclosed gardens of ennobling reflection and creation, universities encompass the wisdom of the past and the hope of the future. Or do they?This critical glossary-written by a group of Princeton graduate students and faculty-defines fifty-eight terms common to academic life in a style that will prick both egos and consciences. From "academia" to "vocation," "canon" to "peer review," "discipline" to "methodology," the book scrutinizes the often stultifying structures of modern disciplinary life, calls out a slavish devotion to "knowledge production" as the enemy of thought, and even dissects the notion of "academic excellence."Feisty and darkly funny, passionate and deeply insightful, this book raises hard questions about teaching, research, theory, practice, and academic labor. The result is a must-read dispatch from today's academic trenches-one that is sure to provoke discussion and debate.